GAMBARAN PERILAKU MENCARI BANTUAN PSIKOLOGIS PROFESIONAL PADA SAMPEL MAHASISWA INDONESIA DENGAN INDIKASI GANGGUAN MENTAL UMUM - Rahmah Saniatuzzulfa; Nurul Hartini; Fitri Andriani (Jurnal Psikohumanika, 2026)
The purpose of this study was to analyze the behavior of seeking professional psychological help among college students in Indonesia. This study employed a quantitative descriptive method, utilizing a survey that involved 106 respondents. This study used the SRQ-20 instrument to screen for indications of Common Mental Disorders and the AHSQ to explore help-seeking behavior. The results showed that 51 respondents met the criteria for common mental disorders. Most of them were aware that the university offered mental health services (78.4%) and considered these services to be vital (86.2%). However, most of them tried to solve the problem themselves (86.3%) or asked friends for help (82.4%) to solve the problem. Only a few sought professional mental health help (31.3%), as they considered the problem to be simple (59%) or due to cost constraints (41.2%). The factors that encourage students to seek help from professionals are the belief that they will find solutions to their problems from mental health professionals (39.2%) and the need to get help from mental health professionals (37.3%). This study can be used as information to improve the behavior of seeking professional psychological help among students with indications of common mental disorders.